The Role of Notary Position Regulations in Improving the Integrity and Professionalism of Notaries in Indonesia - Markus Gunawan; Ali Amran; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the role of Indonesian Notary Position Regulations (UUJN) in enhancing integrity and professionalism within the notarial profession in Indonesia. The study adopts a normative legal research methodology, integrating both statutory and conceptual approaches to evaluate the effectiveness of existing regulatory frameworks governing notarial practice. Primary objectives include analyzing the impact of current regulations on notarial standards, identifying implementation challenges, and developing recommendations for regulatory enhancement. The research findings demonstrate that while the UUJN serves as a crucial foundation for professional notarial practice, several significant challenges persist in its implementation. These challenges encompass technological adaptation requirements, increasing transaction complexity, and the need for stronger oversight mechanisms. Analysis reveals opportunities for regulatory refinement to address emerging professional demands while maintaining high standards of integrity. This study contributes to the existing body of knowledge by providing comprehensive insights into the relationship between regulatory frameworks and professional excellence in notarial practice. The findings lead to specific recommendations for regulatory enhancement, including strengthening supervisory mechanisms, developing continuous professional development programs, and harmonizing standards with international best practices. These recommendations aim to foster a more robust and adaptable notarial profession in Indonesia while maintaining its fundamental role in ensuring legal certainty and protection for society.